Curriculum development and evaluation in nursing - Keating, Sarah B. (Springer Publishing Company, 2015)
This third edition of the leading nursing text on curriculum development and evaluation continues to address relevant NLN and AACN core competencies for curricula in all undergraduate and graduate nursing programs. Written for graduate students and faculty, this new edition responds to the many changes that have occurred in nursing and education since the second edition was published. These include the continued shortage of nursing faculty and the projected additional losses of experienced faculty due to impending retirements, as well as the implementation of the Affordable Care Act and Consensus Model for Advanced Practice Nursing. This third edition covers curriculum development and evaluation in detail and provides the knowledge and practical applications needed by new and experienced faculty to confidently embrace the academic role. With an emphasis on interdisciplinary collaboration throughout, the text focuses on the growth of simulation, guidance for new faculty transitioning from a clinical to academic role, developing curricula for practice and academic settings, program evaluation, accreditation activities, and recommendation for research in nursing education. Also addressed is the explosion of DNP programs across the country and its effect on practice and education, as well as the controversy surrounding the use of simulation. Chapter objectives, discussion points, learning activities, references and a glossary enhance learning and retention of material. The text is a valuable resource for CNE certification review. -- Provided by publisher.